Ontologi Ekonomi Islam: Membangun Sistem Teologis yang Berbasis Tauhid dan Kepemimpinan Khalifah - Dewi Fazira; Abdul Malik Karim Amrullah; Yogi Pandapotan Siregar; Ahmad Wahyudi Zein (Journal of Islamic Economics and Finance, 2025)
The purpose of this research is to create an ontological framework of Islamic economics with tawhid and caliphate as its philosophical and theological pillars. Islamic economic ontology integrates moral and spiritual elements into the economic system and describes economic reality according to Islamic teachings. The study, which used the literature research method, found that caliphate leadership emphasizes human responsibility in managing natural resources in a just and sustainable way, while the concept of tawhid serves as a theological foundation that places Allah at the center of all economic activities. When these two ideas are combined, it results in a comprehensive strategy that prioritizes material, social, and spiritual well-being. It is hoped that the ontological framework put forward in this study will serve as a roadmap for creating an economic structure that is not only effective but also socially just and consistent with Islamic principles.